Dostosowanie wielkości i struktury rodziny do warsztatu rolniczego w ujęciu statycznym - Chromińska, Maria (Wydział Prawa i Administracji UAM, 1977)
The aim of the paper is the assay of answering the following questions: 1) Does there exist any difference with respect to the average number of born children in families living on farms of different size? 2) How great are the differences in regard to the average birth number according to the mother's age? 3) What are the reasons of these differences? The source of the informations are the investigation results of the general census in 1970 as well as the results of investigation inquiry of the Centre for Demography and Economical Statistics at the Academy of Economics in Poznań according to the state of 31 III 1966. The examined families were divided according to the used farm area and the mothers' age. The investigation results of the census show that the average number of children born by mothers working on their own farms are higher for women living in the country than in town. Mothers — physical and intellectual working women have average lower numbers of children than mothers working on their own farms. The results of inquiry investigations refer to the following voivodeships of: Białystok, Katowice, Koszalin, Kraków, Lublin, Łódź, Olsztyn and Rzeszów. Analysing the age of getting married there was found that for mothers who at the moment of investigating were below 25 years old, from 25 to 34 years and from 35 to 44 years old, the age of getting married increases together with the increase of the size of the used farm area, but for mothers from 45 to 54 years old as well as of 55 years old and more, the age of getting married lowers according to the increase of the size of the used farm area. The average number of children in a peasant family increases with the size of farm area up to the area group of 15-19 ha. In the area group of 20 ha and more the number of children in the family either fluctuates or decreases. Investigating the relation between fertility and the size of farm area there was stated a positive essential relation between the chosen variables for mothers of finished fertility period; for mothers, however under 25 years old, the correlation was low.
The adjustment of largeness and structure of family to the farm field in the statistical meaning